The Influence of Storytelling Apron Media on the Speaking Skills of Children Aged 5-6 Years at TK Karunia, Medan Johor District, Academic Year 2022/2023 - Harahap, Namira Mawaddah; Sariana Marbun (International Journal of Applied and Advanced Multidisciplinary Research, 2023)
This study aims to determine the effect of storytelling media on the speaking skills of children aged 5-6 years. This study uses an approach with an experimental method (Quasi-Experimental Design) in the form of The Equivalent Time Samples Design. The population in this study were all children aged 5-6 years at TK Karunia for the 2023/2024 academic year. From the data the results of data analysis have an average score of treatment 1 of 2.5, treatment 2 gets an average value of 6.1 while treatment 3 gets an average value of 9.3. Based on data analysis through non-parametric hypothesis testing, the SPSS 25 statistical test value is 0.005. There is a significant influence between the use of storytelling media on the speaking skills of children aged 5-6 years at TK Karunia, Medan Johor District, Academic Year 2022/2023.